Функциональный электропроводный композит с керамической матрицей на основе сbn, содержащий нитрид титана - Петруша, И.А.; Туркевич, В.З.; Пальчиков, В.Е.; Осипов, А.С.; Смирнова, Т.И.; Романко, Л.А.; Фесенко, И.П.; Гажа, Г.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Cubic BN−TiN ceramic composite of 25 vol. % TiN content was fabricated at high pressure
(7,7 GPa) and its physical properties of density, specific electric resistance, thermal conductivity, bulk modulus, strength and hardness were evaluated to examine the potential of these ceramics as new functional material (windows for liquid-metal target) and wear-resistant tool material.